PACING STRATEGY IN SPEED SKATING: INFLUENCE OF THE GENDER AND RACE'S PERFORMANCE LEVEL IN 1500-M DISTANCE - Carlos Rafaell Correia-Oliveira; Mayara Vieira Damasceno; Alan de Albuquerque Melo; Rômulo Bertuzzi; Maria Augusta Peduti Dal’Molin Kiss (Journal of Physical Education)
ABSTRACT Our aim was to analyze the pacing strategy adopted during middle-distance speed skating and to verify the influence of gender and race's performance level on pacing adopted. The races of male and female athletes during five stages of a World Cup, season 2009/2010, were included in the study. In both genders, the races were classified as high (HP) and low (LP) performance. The pacing adopted was similar between genders, with male athletes being faster throughout the race (P < 0.05). In both genders, the HP races were more aggressive in all intervals compared to LP races (P < 0.05), regardless of gender. Although performance is different between genders, the pacing adopted was similar between them in faster and slower races, suggesting that the technical in elite athletes seems to be a determinant factor in choice of adopted pacing strategy.